Supply chain strategies and disaster planning - Venkataraman, Ray R.; Pinto, Jeffrey K. (Los Angeles, CA : SAGE Publications, Inc., 2017)
This case illustrates how firms should formulate and implement global operations and supply chain strategies for risk management to alleviate disruptions to their operations and supply chains from natural disasters or safety and security problems. The fact that only 10% of businesses have contingency plans in place to cope with operations and supply chain disruptions despite the likelihood of disasters means disaster planning/risk management should be an essential part of their supply chain strategy.
Originally published in Venkataraman, R. R., & Pinto, J. K. (2017). Supply chain strategies and disaster planning. In Operations management: Managing global supply chains (pp. 57-58). Thousand Oaks, CA: SAGE Publications. ISBN: 9781506302935.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Emergency management